Quality and Efficiency of Health Services in The Implementation of Electronic Medical Records: Bibliometric Analysis - Maryati, Warsi; Hartono, Hartono; Puspita Febrinasari, Ratih (Proceeding of the International Conference Health, Science And Technology (ICOHETECH), 2024)
Background: Electronic medical records (EMR) were growing rapidly because they were believed to improve the quality and efficiency of health services. Literature studies related to EMR have been carried out, but the bibliometric analysis was not yet known. This study aimed to analyze the bibliometrics of research related to EMR and its impact on quality and patient care. Methods: We have carried out bibliometric analysis using VOS viewer and Mendeley on articles from the Scopus database for 2014-2023. Articles have been filtered based on the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) diagram. We used the keywords electronic medical records, quality and efficiency to search for articles. Articles that were not in English, could not be downloaded in full text and were not related to quality or efficiency were excluded. Articles that met the criteria were analyzed. Results: We obtained 24 articles from the screening results. Most articles in 2020 (6), there was a significant increase in 2019 (4). Most articles have been published in Journal of Medical Internet Research (3). The International Journal of Medical Informatics received the most citations (160 from 2 articles). There were 8 research articles from the United States. The most frequently used keywords were electronic medical record(s). Meanwhile, the issues most commonly associated with the implementation of EMR include; quality improvement, health care quality, patient satisfaction, and cost. Conclusion: Bibliometric analysis was important to carry out in future research to map the characteristics of research with wider data sources.